Akurasi Metode Penilaian Konsumsi Pangan sebagai Pengukuran Asupan Mikronutrien pada Remaja: Scoping Review: Accuracy of Dietary Assessment Methods as a Measurement of Micronutrient Intake in Adolescents: Scoping Review - Simatupang, Abdul Malik; Dewi, Yulia Lanti Retno; Andayani, Tri Rejeki (Amerta Nutrition, 2024)
Background: Micronutrient deficiency, including iron, vitamin A, B-12 and folic acid, can cause anemia and harm adolescent health. Accurate dietary assessment methods is crucial to detect micronutrient deficiencies, but existing methods, have limitations, necessitating a review to identify the accurate methods for assessing micronutrient intake in adolescents. Objectives: To determine the accuracy of dietary assessment methods as suitable option for measuring micronutrient intake in adolescents. Methods: This study utilized the Preferred Reporting Items for Systematic Review and Meta-Analysis extension for Scoping Review (PRISMA-ScR) flowchart approach. Article were identified from ScienceDirect, PubMed, Scopus, Google Scholar. Articles were included if participants aged 10-19 years, published between 2014-2024, written in English/Indonesian, original research articles and studies related to validation of dietary assessment methods for micronutrient intake. The keywords were "micronutrient intake" OR "dietary intake" AND "dietary assessment" OR "validity" AND "adolescent". Discussions: 1157 articles were identified, 7 met the eligibility criteria, including 50 to 1081 adolescent. The Semi-Quantitative Food Frequency Questionnaire (SQ-FFQ) method was valid for sodium, niacin, folate, thiamine, calcium, phosphorus and reproducible for vitamin A, vitamin C, thiamine, riboflavin, niacin, iron, calcium, phosphorus, potassium, β-carotene. The Food Frequency Questionnaire (FFQ) method was valid for riboflavin, vitamin C, calcium, serum iron biomarkers, and reproducible for retinol, thiamine, riboflavin, vitamin C, vitamin D, iron, calcium. The 24-hour Dietary Recall (24hDR) method showed acceptable validity for serum iron biomarkers. Conclusions: The SQ-FFQ, completed by adolescents with instruction of nutritionist, using a shorter food list and time intervals, has higher relative validity and reproducibility.